Implikasi Putusan World Trade Organization terhadap Larangan Ekspor Nikel Indonesia oleh Uni Eropa - Jason, Ferdinand; S Shahrullah, Rina; Syarief, Elza (Jurnal Supremasi, 2024)
Indonesia as a member of the World Trade Organization (WTO) is bound by the General Agreement on Tariffs and Trade (GATT) and WTO regulations. In an effort to increase domestic raw material processing, Indonesia implemented an export ban on nickel ore and other minerals. However, this action sparked protests from the European Union, leading to a lawsuit filed with the WTO. This article analyzes the WTO decision in the context of international trade principles, examining its legal applicability in Indonesia and its impact on other types of minerals. The research method used is a normative legal approach or doctrinal research. The final decision of the WTO dispute settlement panel declared that Indonesia's policy of export bans and mandatory processing of nickel minerals violated Article XI.1 of the GATT 1994. Nevertheless, Indonesia appealed the decision and remains committed to the nickel ore export ban to advance the economy and welfare of its people. Thus, this policy represents a bold step towards downstream the mining industry.